Description of a large specimen of Paralepis elongata (Brauer, 1906) from Angola, southeastern Atlantic Ocean (Aulopiformes: Paralepididae) - Ho, Hsuan-Ching; Iwamoto, Tomio (Zootaxa, 2024)
The elongate barracudina, Paralepis elongata (Brauer, 1906), received limited attention in the past, with only a few individuals documented, mostly in publications focusing on the feeding habits of large predatory pelagic fishes. Furthermore, the taxonomic history of the species is complicated, with some earlier sources providing incorrect information that influenced subsequent works. As a result, the accurate distribution range of P. elongata remains uncertain. An adult male specimen of P. elongata, representing the largest known individual, is reported from off Angola, southeastern Atlantic. A detailed description is provided, and the literature records of the species are reviewed and discussed.